2003
DOI: 10.1046/j.1365-2036.2003.01454.x
|View full text |Cite
|
Sign up to set email alerts
|

NSAIDs, gastroprotection and cyclo‐oxygenase‐II‐selective inhibitors*

Abstract: Summary In patients at high risk of NSAID‐associated serious upper gastrointestinal complications, gastroprotection with misoprostol or a proton pump inhibitor should be considered. Only misoprostol, 800 µg/day, has been shown to reduce serious upper gastrointestinal complications in a large clinical outcome trial. The benefit of Helicobacter pylori eradication in reducing NSAID‐associated gastrointestinal toxicity is controversial, and routine testing for and eradication of H. pylori in NSAID users are not cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(40 citation statements)
references
References 46 publications
1
37
0
2
Order By: Relevance
“…Inhibition of cell division and alteration of the cell cycle distribution were observed in cultured colon cancer cells, tumor cells were arrested in G 0 /G 1 phase, and finally undergoing apoptosis. Furthermore, etodolac was found to inhibit COX-2 associated PGE 2 synthesis in HT-29/Inv3 cell lines (26,27). In this study, the effect of the NSAID, etodolac, a 1,8-diethyl-1,3,4,9-tetrahydro-pyrano (3,4-ß) indole-1-acetic acid (Fig.…”
Section: Introductionmentioning
confidence: 60%
“…Inhibition of cell division and alteration of the cell cycle distribution were observed in cultured colon cancer cells, tumor cells were arrested in G 0 /G 1 phase, and finally undergoing apoptosis. Furthermore, etodolac was found to inhibit COX-2 associated PGE 2 synthesis in HT-29/Inv3 cell lines (26,27). In this study, the effect of the NSAID, etodolac, a 1,8-diethyl-1,3,4,9-tetrahydro-pyrano (3,4-ß) indole-1-acetic acid (Fig.…”
Section: Introductionmentioning
confidence: 60%
“…Gastrointestinal toxicity of NSAIDs has been alleviated by developing molecules that are selective for the inducible isoform (COX-2) over the constitutive form (COX-1) (Laine, 2002;Pronai et al, 2003, Laporte et al, 2004Micklewright et al, 2003). It has been suggested that GI toxicity arises when both COX-1 and COX-2 enzymes are inhibited, and that inhibiting either one alone does not cause injury to the gastrointestinal mucosa (Takeuchi et al, 2003;Tanaka et al, 2002aTanaka et al, , 2002b.…”
Section: Drug Signatures For the Acute Phase Responsementioning
confidence: 99%
“…Recent studies suggest that coxibs (cyclooxygenase-2-selective inhibitors) have a favorable safety profi le regarding the gastrointestinal tract [10][11][12] . However, longerterm gastrointestinal data from the celecoxib study (CLASS) have questioned the risk-benefi t profi le of these drugs [13] .…”
mentioning
confidence: 99%